Cross-cultural Negotiation Conflicts: The Myanmar Case - Sasne Grosz, Annamaria; Jozsa, Laszlo; Maung, Sandi (International Review of Management and Marketing, 2023)
The economic role of Southeast Asia has deeply changed in the past decades therefore Central European companies turned to collaborate with many of them. However, the cultural differences can lead to fiasco. We focused on understanding the role of cultural background in business negotiation and potential conflicts of international businesses. In the qualitative phase, we looked for entrepreneurs and corporate professionals in Southeast Asia who (1) were native to the country and had contact with the European business world; (2) were European businesspeople operating in Southeast Asia. We prepared in-depth interviews with 10 people where questions concerned the differences between cultures, their business role, and personal experiences. We found that the business culture of the studied countries is primarily determined by the values ​​of the Buddhist religion, characterized by a highly hierarchical structure and a large distance of power. The stable foundation of businesses is family relationships, they operate in a centralized way, characterized by one-person decision-making. Outsiders are not allowed access to the business, resulting in very low transparency. Due to some similarities between Central European business habits and Burmese culture cooperation is possible. Beside the description of a seldom studied country’s business style, potential conflict situation was determined.